El Immortal - Moncada-Rodriguez, Mercedes (Spain : Moncada-Rodriguez, Mercedes, 2005)
In 1979 in Nicaragua there occurred the uprising of the Sandinistas, who overthrew the long running dictatorship of the Somozas. The government of the United States at that time was afraid that there would emerge a "second Cuba" in the region and began to organize and finance the anti-revolutionary movement of the Contras. The following civil war, in which over 50,000 people died, affected the lives of almost every Nicaraguan family. The members of the Rivera family's lives were forever changed in 1983, when their village was raided by the Contra units, who burned their house, abducted the twelve year-old José Antonio and his older sister Reina, and drafted them both into the army. Through the story of one family the film reveals how deeply war can affect the lives of ordinary people.
Duration: 01:17:00
Keywords: Documentary films